Supporting Project-Based Learning through Economical and Flexible Learning Spaces - Jesse Eickholt; Vikas Jogiparthi; Patrick Seeling; Quintrese Hinton; Matthew Johnson (MDPI AG, 2019)
Project-based learning often centers learning experiences around projects and is characterized by the application of knowledge, management of resources, and self-directed learning. In recent years, newer classroom designs have been developed to facilitate communication, classroom interaction and active learning but the cost of such spaces can be prohibitive. Here we present two economical options for flexible learning spaces that support the aims of project-based learning and cost much less than typical active learning classroom models. In a quasi-experimental study, one of our economical active learning environments was paired with a traditional classroom and a prototypical active learning classroom. These learning environments were used in a CS2 course that employed a group-based, active learning pedagogy centered on in-class projects. Students’ perceptions were gathered on the classrooms and their supporting technology. Between the economy and prototypical active learning environment, no significant differences were found in students’ perceptions of the space as it related to collaboration and supporting learning. Results from accompany focus groups indicates that the space was conducive to their learning and helped them engage with peers. These economical and flexible options support the aims of project-based learning at a reduced cost.